Resequencing And Nucleotide Variation Of Sucrose Synthase (Nmsusy1) Gene In A Tropical Timber Tree Neolamarckia Macrophylla - Tan, C.J; Ho, W.S; Pang, S.L (IJSTR, 2014)
Sucrose synthase (SuSy) is a key enzyme that catalyses the reversible synthesis and degradation of sucrose. It provides greater impact in regulating the photosynthetic processes and environmental stresses in plants. Thus, the nucleotide variation of partial NmSusy1 genomic DNAs (750 bp) generated through PCR amplification was examined in this study, and this followed by resequencing from 15 selected Neolamarckia macrophylla clones. The consensus sequences were aligned to detect the presence of single nucleotide polymorphisms (SNPs). In total, five SNPs were detected at nucleotide 1, 2, 34, 35 and 397. Of these, four SNPs were located at the predicted coding region while one SNP was located at the predicted non-coding region. Interestingly, one single base pair InDel polymorphism was also detected at nucleotide 17. On average, one SNP at every 150 bp was detected based on the 15 NmSusy1 sequences. There was one non-synonymous mutation detected, whereby amino acid glutamic acid (E) was replaced by arginine (R) in one of the 15 samples tested. This non-synonymous SNP might change the structural, functional or biochemical properties of the enzyme being produced and therefore possibly lead to changes in phenotypic characteristic of the trees. Overall, this study has demonstrated that resequencing is an effective technique for classifying molecular diversity or nucleotide variation in the Susy gene of N. macrophylla. Those SNPs, once validated, could potentially be used as a tool in marker-assisted selection (MAS) that enables more precise and accurate in the selection and prediction of yield or performance at the early developmental stages, such as at the seedling stage.